(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
Mergers and acquisitions (M&A) play a central role in corporate restructuring and economic development in the United States. This article examines the legal framework governing corporate combinations within the U.S. legal system, focusing on consensual transactions, tender offers, and shareholder rights under corporate and securities law. The analysis explores common transaction structures, including stock purchases, asset acquisitions, and various merger forms, as well as the regulatory oversight imposed by federal securities and antitrust laws. Particular attention is given to the role of shareholder voting, appraisal rights, and disclosure obligations under the Delaware corporate law regime. The article also discusses contemporary developments affecting M&A activity, such as private equity transactions, special purpose acquisition companies (SPACs), and emerging technological sectors such as artificial intelligence and blockchain-based enterprises.